Smart control of traffic light system using image processing / Mutmainnah Radhiah Mohamad Jeffery ... [et al.] - Mohamad Jeffery, Mutmainnah Radhiah; Meng, Belinda Chong Chiew; Damanhuri, Nor Salwa; Othman, Nor Azlan; Awang Damit, Dayang Suhaida (2020)
Traffic congestion at junctions has become a serious issue among motorists due to the growing number of registered vehicles in Malaysia. Traffic light is commonly used to control the flow at road junction. Pretime and count down timers are widely used in traffic light control system. Often, this control system unable to handle heavy traffic flows due to fixed-time setting and cause traffic jam. Therefore, there is a need of adaptive traffic signals which are able to perform real time monitoring of traffic density. This study proposed a system that uses image processing in controlling the traffic flow in an effective manner by taking images of each lane at a junction. The system applies image processing technic determine the priorities of green signal based on real time traffic density. Edge detection is used to detect the density of traffic at each lane. More time is allocated for the vehicles on the densest road to pass compared to other less dense road. Arduino is used as a microcontroller to control the changes of each signal of the traffic lights based on the traffic density. Smart traffic light system could bring benefits to smooth motion of vehicles in the transportation routes.